Avoidance of axillary lymph node dissection in selected patients with node-positive breast cancer - Noguchi, M. (European journal of surgical oncology, 2008)
Currently, it is standard practice to avoid ALND in patients with negative SLN, whereas this procedure is mandated for those with positive SLN. However, there has been some debate regarding the necessity of complete ALND in all patients with positive SLN. This review article discusses the issues related to eliminating the need for ALND in selected patients with positive nodes. A review of the English language medical literature was performed using the MEDLINE database and cross-referencing major articles on the subject, focusing on the last 10 years. Currently, complete ALND is mandated in patients with SLN macrometastases as well as those with clinically positive nodes. It is not clear whether SLN biopsy is appropriate for axillary staging in patients with initially clinically positive nodes (N1) that become clinically node-negative (N0) after neoadjuvant chemotherapy. Although there is debate regarding whether ALND should be performed in patients with micrometastases in the SLN, it seems premature to abandon ALND in clinical practice. Moreover, it remains unclear whether it is appropriate to avoid complete ALND in patients with ITC-positive SLN alone. In the absence of data from randomised trials, the long-term impact of SLN biopsy alone on axillary recurrence and survival rate in patients with SLN micrometastases as well as those with ITC-positive SLN remains uncertain. These important issues must be determined by careful analysis of the results of ongoing clinical trials.